Assessment of the acute toxicity of ethanol extract from the rhizomes of Iris scariosa L. in mice - Aitkenova, Ailazzat A.; Atazhanova, Gayane A.; Badekova, Karakoz Zh.; Samorodov, Aleksandr V.; Akhmetova, Saule B.; Ishmuratova, Margarita Yu.; Karilkhan, Islambek; Tazhina, Arailym A.; Sydykova, Ainur Zh. (Frontiers in Pharmacology, 2026)
BackgroundPlants of the genus Iris L. (Iridaceae) attract the attention of researchers as a source of biologically active phenolic compounds with pronounced antioxidant, anti-inflammatory, and cytoprotective properties. However, the toxicological assessment of individual species, including Iris scariosa L., remains limited, which hinders their pharmaceutical development.AimThe aim of this study was to evaluate the acute oral toxicity of ultrasonic ethanol extract of I. scariosa rhizomes in laboratory mice in accordance with OECD Guideline 425 (2001) and the regulatory requirements of the Ministry of Health of the Republic of Kazakhstan.MethodsThe extract was administered once intragastrically at doses of 500, 1000, and 2000 mg/kg, followed by 14 days of observation of clinical status, body weight dynamics, hematological, biochemical, and histomorphological parameters.ResultsNo fatalities were recorded. Blood parameters remained within physiological norms (p > 0.05). At the maximum dose, a slight, statistically insignificant increase in ALT and AST activity was observed, reflecting a compensatory response of hepatocytes without signs of cytolysis. Histopathological analysis revealed moderate reversible changes in renal tissue, characterized by vacuolization of the tubular epithelium, venous hyperemia, and mild inflammatory infiltration, while maintaining normal glomerular structure and absence of fibrosis. The morphology of the liver, pancreas, heart, and spleen remained unchanged.ConclusionAccording to the OECD/GHS classification, I. scariosa extract is classified as a Category V substance (LD50 > 2000 mg/kg), which indicates low acute oral toxicity and good tolerability. The morphological reactions observed are temporary and adaptive in nature, probably associated with the biphasic response of phenolic compounds. The results confirm the safety of the extract and the need for further study of its chronic toxicity.